Low tensile strength high manganese steel for lng fuel tank and method of manufacturing the same
Patent Information
- Application Number
- CN202610948504.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]旨在解决上述常用技术中如何在保证优异超低温韧性的前提下,将LNG燃料罐用高锰钢的抗拉强度降低至700MPa以下,进而克服传统高锰钢因强度过高而导致的加工成形困难的技术问题,本发明提供了一种LNG燃料罐用低抗拉强度高锰钢,以质量分数计,其化学组成包括:C 0.15~0.22%,Si 0.12~0.16%,Mn 23~24%,Al 1.3~2.1%,余量为Fe和不可避免的杂质
本发明采用低碳设计(C 0.15%~0.22%)作为降低抗拉强度的核心手段,从源头上弱化了间隙固溶强化效应。但低碳在降低强度的同时会带来下述壁垒:奥氏体稳定性下降、层错能降低诱发TRIP效应产生马氏体(反而推高强度并损害韧性)。
Smart Images

Figure CN122918445A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of steel materials technology, specifically relating to a low tensile strength high manganese steel for LNG fuel tanks and its preparation method. Background Technology
[0002] With the continued growth in global demand for clean energy, the storage and transportation needs of liquefied natural gas (LNG), as a low-carbon and clean energy source, are expanding. In the transportation sector, LNG heavy-duty trucks can reduce nitrogen oxide emissions by 50% to 80% and particulate matter emissions by 80% to 95%, playing a significant role in improving air quality in densely populated logistics areas such as urban peripheries. In recent years, many provinces and cities have introduced policies to encourage or mandate the replacement of diesel heavy-duty trucks with LNG heavy-duty trucks, directly driving a surge in demand for steel used in LNG fuel tanks. Currently, the mainstream materials for LNG storage tanks include austenitic stainless steel, aluminum alloys, and 9Ni steel. However, Ni is an important alloying element in austenitic stainless steel and 9Ni steel, and its price is expensive and fluctuates wildly, significantly increasing the manufacturing cost of storage tanks. Aluminum alloys have low strength and hardness, are prone to large deformation during welding, and have poor wear resistance, limiting their application in components that need to withstand friction or impact. High-manganese steel, which uses Mn to replace expensive Ni as an austenitic stabilizing element, can significantly reduce raw material costs while also possessing good low-temperature resistance, thus becoming a highly competitive alternative material.
[0003] However, existing high-manganese steels have significant technical drawbacks when applied to LNG fuel tanks for vehicles. On one hand, traditional high-manganese steel generates hard, brittle martensite during deformation via the TRIP effect, utilizing martensitic phase transformation to increase strength, resulting in generally high tensile strength. For example, the tensile strength of high-manganese steel used in existing LNG storage tanks can reach over 730 MPa, and in some cases even exceeds 860 MPa, far exceeding the upper limit of material strength requirements for the inner components of LNG fuel tanks. This excessive strength makes cold forming processes such as rolling and stamping extremely difficult, requiring more powerful equipment, and may necessitate stress-relieving heat treatment after forming, significantly increasing manufacturing costs and process complexity. On the other hand, the martensitic phase generated by the TRIP effect severely impairs the low-temperature toughness and plasticity of high-manganese steel. Studies have shown that high-manganese steel is prone to intergranular fracture under ultra-low temperature conditions. Since the inner components of LNG fuel tanks for vehicles must withstand ultra-low temperature environments of -196°C for extended periods during service, insufficient low-temperature toughness will pose a safety risk of brittle fracture. Therefore, how to effectively control the tensile strength within a reasonable range while ensuring excellent ultra-low temperature toughness is a problem that has not yet been solved by existing technologies.
[0004] Therefore, it is necessary to provide a low tensile strength high manganese steel for LNG fuel tanks and its preparation method to alleviate or solve the above problems. Summary of the Invention
[0005] Aiming to solve the technical problem of how to reduce the tensile strength of high-manganese steel for LNG fuel tanks to below 700 MPa while ensuring excellent ultra-low temperature toughness, and thus overcome the technical difficulties in processing and forming caused by the excessive strength of traditional high-manganese steel, this invention provides a low tensile strength high-manganese steel for LNG fuel tanks. Its chemical composition, by mass fraction, includes: C 0.15~0.22%, Si 0.12~0.16%, Mn 23~24%, Al 1.3~2.1%, with the balance being Fe and unavoidable impurities.
[0006] Furthermore, the yield strength is 240~280MPa, the tensile strength is 620~670MPa, the impact absorption energy of the steel in the ultra-low temperature Charpy impact test along the rolling direction at -196℃ is 130~160J, and the elongation after fracture is 55~65%.
[0007] This invention provides a method for preparing low tensile strength high manganese steel for LNG fuel tanks, comprising the following steps: The molten steel is obtained, and its chemical composition, by mass fraction, includes: C 0.15~0.22%, Si 0.12~0.16%, Mn 23~24%, Al 1.3~2.1%, with the balance being Fe and unavoidable impurities; The molten steel is subjected to casting, heating, rolling and cooling processes in sequence to obtain the low tensile strength high manganese steel for the LNG fuel tank.
[0008] Furthermore, obtaining molten steel includes: smelting the raw materials under a protective atmosphere to obtain the molten steel, wherein the smelting temperature is 1600~1650℃.
[0009] Furthermore, the casting process includes: pouring the molten steel into a mold at 1470~1500℃ to obtain an ingot.
[0010] Furthermore, the temperature of the heat treatment is 1150-1250℃, and the duration of the heat treatment is 1.5-2.5h.
[0011] Furthermore, the initial rolling temperature during the rolling process is 1120~1150℃, and the final rolling temperature is 935~960℃.
[0012] Furthermore, the total reduction rate during the rolling process is 75-85%.
[0013] Furthermore, the starting temperature during the cooling process is 940~950℃, and the cooling rate is 20~40℃ / s.
[0014] Furthermore, the LNG fuel tank is made of low tensile strength high manganese steel with a thickness of 12±1 mm.
[0015] Compared with the prior art, the present invention has at least the following advantages: This invention employs a low-carbon design (C 0.15%~0.22%) as the core means to reduce tensile strength, thereby weakening the interstitial solid solution strengthening effect from the source. However, while reducing strength, low carbon also brings the following barriers: decreased austenite stability and reduced stacking fault energy induce the TRIP effect to produce martensite (which in turn increases strength but impairs toughness).
[0016] To this end, the present invention precisely increases the Mn content to 23.2%~23.6% and adds an appropriate amount of Al 1.3%~2.1% to compensate for the loss of austenite stabilization due to the reduction of carbon, thereby regulating the stacking fault energy to the TWIP effect window and suppressing the martensitic phase transformation; at the same time, it strictly controls the Si content at a low level of 0.12%~0.16% to avoid superimposing the effect of low carbon on the reduction of stacking fault energy.
[0017] The synergistic effect of the above components makes the tensile strength in the embodiments of the present invention stable at 627.5~664.4MPa (all not greater than 700MPa), the impact absorption energy at -196℃ reach 135.8~159.5J, and the elongation is 58.1%~60.6%, achieving comprehensive performance of low strength, high toughness and excellent plasticity.
[0018] In comparison, Comparative Example 1 (without Al) has a tensile strength as high as 863.5 MPa and an impact energy of only 95 J, while Comparative Example 2 (low Mn, insufficient Al, high Si) has a tensile strength of 860.3 MPa and an impact energy of only 78 J, which proves the indispensability of the synergistic cooperation of various characteristics. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0020] Figure 1 The image shows the metallographic structure of the high-manganese steel obtained in Example 2 of this invention. Figure 2 The EBSD phase diagram of the high-manganese steel obtained in Example 2 of this invention; Detailed Implementation The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] Furthermore, the technical solutions of the various embodiments of the present invention can be combined with each other, but only if they are based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.
[0022] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in the present invention, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this invention, as well as the prior art known to those skilled in the art and the description of the invention, may be implemented using any prior art methods, devices, and materials similar to or equivalent to the methods, devices, and materials in the embodiments of the present invention.
[0023] This invention provides a low tensile strength high manganese steel for LNG fuel tanks, whose chemical composition by mass fraction includes: C 0.15~0.22%, Si 0.12~0.16%, Mn 23~24%, Al 1.3~2.1%, with the balance being Fe and unavoidable impurities.
[0024] Carbon is the most effective interstitial solid solution strengthening element in steel. Existing high-manganese steels generally adopt a high-carbon design (usually ≥0.30%) to pursue high strength, significantly improving strength through the solid solution strengthening effect of carbon. This invention takes the opposite approach, significantly reducing the carbon content, weakening the degree of interstitial solid solution strengthening from the source, and laying the most basic chemical composition prerequisite for controlling the tensile strength below 700MPa.
[0025] However, reducing carbon is not simply a matter of reduction. While lower carbon content reduces strength, it also presents the following technical barriers: First, carbon is a strong austenite stabilizing element; reducing carbon content leads to a shrinkage of the austenite phase region, decreased austenite stability, and an increased risk of martensitic transformation. Second, carbon increases stacking fault energy; lower carbon content reduces this energy, making it easier to induce the TRIP effect and produce hard, brittle martensite. Martensitic transformation is precisely the strengthening mechanism that this application aims to avoid—it both increases tensile strength and severely impairs low-temperature toughness. Therefore, low-carbon design must be combined with a series of targeted technical features to compensate for these effects in order to achieve the goal of reducing strength without sacrificing toughness.
[0026] To address the issues of decreased austenite stability and reduced stacking fault energy caused by low carbon content, this invention solves these problems by precisely increasing the Mn content to 23.2%~23.6% and adding an appropriate amount of Al 1.3%~2.1%.
[0027] Mn is also a strong austenite stabilizing element. This invention controls the Mn content within an extremely narrow high-range to replace the austenite stabilizing effect lost due to reduced carbon content, ensuring the acquisition of a single-phase austenite structure at room temperature. Simultaneously, Mn effectively increases the stacking fault energy, working synergistically with an appropriate amount of Al to pull the stacking fault energy back from the decreasing trend caused by low carbon to the TWIP effect window. This transforms the deformation mechanism from the harmful TRIP effect to the beneficial twin-induced plasticity, thereby fundamentally suppressing the increase in strength and the deterioration in toughness caused by martensitic phase transformation.
[0028] Furthermore, this invention strictly controls the Si content at a low level of 0.12% to 0.16%. This is because Si reduces the stacking fault energy, and this effect is superimposed on the reduction of stacking fault energy caused by low carbon content. If the Si content is too high, the stacking fault energy will be further pushed into the TRIP range. Therefore, setting a low Si content is a necessary complement to the low carbon design, ensuring that the stacking fault energy is not pulled down to the dangerous range by multiple factors.
[0029] Comparative Example 1, while employing low carbon (0.18%) and high Mn (23.1%), lacked any Al, resulting in insufficient stacking fault energy. During deformation, the TRIP effect still occurred, producing martensite, achieving a tensile strength of 863.5 MPa and a low-temperature impact energy of only 95 J. Comparative Example 2, although containing Al, had a severely insufficient content (0.49%) and a high Si content (0.21%), while simultaneously having a low Mn content (19.87%). This resulted in excessively low stacking fault energy, leading to severe martensitic phase transformation, and a tensile strength of 860.3 MPa and an impact energy of only 78 J. This clearly demonstrates that a low-carbon composition must be combined with a complete system of high Mn, appropriate Al, and low Si; none of these components can be omitted.
[0030] For example, in this invention, the carbon content can be 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.20%, 0.21%, 0.22%, or any two of the above values; the manganese content can be 23%, 23.2%, 23.3%, 23.4%, 23.5%, 23.6%, 24%, or any two of the above values; the aluminum content can be 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.1%, or any two of the above values; and the silicon content can be 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, or any two of the above values.
[0031] In some embodiments, the yield strength of the low tensile strength high manganese steel used for LNG fuel tanks is 240~280MPa, the tensile strength is 620~670MPa, the impact absorption energy of the steel in the ultra-low temperature Charpy impact test along the rolling direction at -196℃ is 130~160J, and the elongation after fracture is 55~65%.
[0032] It should also be noted that the Al content in this invention is controlled at 1.3%~2.1%. As a lightweight element, Al has a smaller atomic radius and atomic weight than Fe. After entering the austenite lattice through substitutional solid solution, it effectively reduces the cell mass, thereby reducing the steel density to 7.61~7.75 g / cm³. 3 Compared to conventional LNG storage tanks made of high-manganese steel, it can reduce weight by about 2.6% to 4.4%, further improving energy conservation and emission reduction benefits in mobile storage and transportation scenarios such as vehicle fuel tanks where weight is sensitive.
[0033] This invention provides a method for preparing low tensile strength high manganese steel for LNG fuel tanks, comprising the following steps: The molten steel is obtained, and its chemical composition, by mass fraction, includes: C 0.15~0.22%, Si 0.12~0.16%, Mn 23~24%, Al 1.3~2.1%, with the balance being Fe and unavoidable impurities; The molten steel is subjected to casting, heating, rolling and cooling processes in sequence to obtain the low tensile strength high manganese steel for the LNG fuel tank.
[0034] In some embodiments, obtaining molten steel includes: melting the raw materials under a protective atmosphere to obtain the molten steel, wherein the melting temperature is 1600~1650°C.
[0035] In some embodiments, the casting process includes: pouring the molten steel into a mold at 1470~1500°C to obtain an ingot; and forging the ingot into a billet.
[0036] The heat treatment includes heating the billet to 1150-1250℃ and holding it at that temperature for 1.5-2.5 hours to homogenize it.
[0037] In other embodiments, the casting process includes pouring the molten steel into a mold at 1470~1500°C to obtain an ingot.
[0038] The heat treatment includes: after removing the riser from the ingot, heating it to 1150-1250℃ and holding it at that temperature for 1.5-2.5 hours to perform homogenization treatment.
[0039] In some embodiments, the initial rolling temperature during the rolling process is 1120~1150℃, and the final rolling temperature is 935~960℃.
[0040] For example, the final rolling temperature can be 935°C, 940°C, 945°C, 950°C, 955°C, 960°C, or any range of two of the above values.
[0041] In some embodiments, the total reduction rate during the rolling process is 75-85%.
[0042] In some embodiments, the starting temperature during the cooling process is 940~950℃, and the cooling rate is 20~40℃ / s.
[0043] For example, the cooling rate can be 20℃ / s, 25℃ / s, 30℃ / s, 35℃ / s, 40℃ / s, or any range of two of the above values.
[0044] In some embodiments, the thickness of the low tensile strength high manganese steel used for the LNG fuel tank is 12±1 mm.
[0045] It should also be noted that while reducing carbon content weakens solid solution strengthening, it also weakens the pinning effect of carbon on grain boundaries, making it easier for grains to grow abnormally during high-temperature heating and rolling. Coarsened grains severely impair ultra-low temperature toughness. To address this technical problem, this invention precisely controls the rolling temperature and cooling regime: by controlling the final rolling temperature at 935~960℃, it ensures complete dynamic recrystallization of austenite to obtain a uniform and fine equiaxed grain structure, while avoiding excessive grain coarsening due to excessively high temperatures; rapid cooling to room temperature at a moderate cooling rate of 20~40℃ / s freezes the recrystallized structure in time, preventing further grain growth or precipitation of harmful phases during slow cooling. Simultaneously, a forging process is added after casting, combined with a homogenization treatment at 1200℃ for 2 hours, to fully break down the as-cast structure and improve the microscopic segregation of elements such as Mn and C, avoiding abnormal local grain growth caused by segregation.
[0046] Under the synergistic effect of the above processes, the resulting high-manganese steel has a uniform equiaxed austenite microstructure with moderate grain size, which further ensures that the tensile strength is not greater than 700MPa, while the impact absorption energy at -196℃ reaches 130~160J.
[0047] In some embodiments, the cross-sectional dimensions of the blank are 65 × 65 mm. 2 .
[0048] To facilitate a further understanding of the present invention by those skilled in the art, the following examples are provided: Example 1 The chemical composition of low tensile strength high manganese steel for LNG fuel tanks, by mass fraction, is: C: 0.15%, Si: 0.12%, Mn: 23.60%, Al: 1.30%, with the balance being Fe and unavoidable impurities.
[0049] The preparation method of low tensile strength high manganese steel for LNG fuel tanks includes the following steps: Obtaining molten steel: According to the above-mentioned composition ratio of high manganese medium-thick plates for LNG fuel tanks, vacuum induction smelting is carried out, and argon gas is used for protection during the smelting process to obtain molten steel.
[0050] Casting process: After alloying, refine for 8 minutes and cool the molten metal to about 1500°C, then pour it into a steel mold to obtain a 20kg ingot.
[0051] The cast steel ingot is forged into a cross-sectional shape with dimensions of 65×65 mm. 2 The blank.
[0052] Heat treatment: The billet is heated to 1200℃ in the furnace and held for 2 hours to achieve thorough homogenization.
[0053] Rolling process: The heated billet is subjected to controlled rolling in the fully recrystallized zone with an initial rolling temperature of 1136℃, a final rolling temperature of 940℃, and a total reduction of 81.5%, to obtain hot-rolled steel with a thickness of 12mm. Cooling treatment: The hot-rolled steel is water-cooled to room temperature; the starting temperature of the cooling is 940℃ and the cooling rate is 40℃ / s, to obtain high-manganese medium-thick plates for LNG fuel tanks.
[0054] Example 2 The chemical composition of low tensile strength high manganese steel for LNG fuel tanks, by mass fraction, is: C: 0.15%, Si: 0.12%, Mn: 23.50%, Al: 1.55%, with the balance being Fe and unavoidable impurities.
[0055] The preparation method of low tensile strength high manganese steel for LNG fuel tanks includes the following steps: Obtaining molten steel: According to the above-mentioned composition ratio of high manganese medium-thick plates for LNG fuel tanks, vacuum induction smelting is carried out, and argon gas is used for protection during the smelting process to obtain molten steel.
[0056] Casting process: After alloying, refine for 8 minutes and cool the molten metal to about 1500°C, then pour it into a steel mold to obtain a 20kg ingot.
[0057] The cast steel ingot is forged into a cross-sectional shape with dimensions of 65×65 mm. 2 billet Heat treatment: The billet is heated to 1200℃ in the furnace and held for 2 hours to achieve thorough homogenization.
[0058] Rolling process: The heated billet is subjected to controlled rolling in the fully recrystallized zone with an initial rolling temperature of 1125℃, a final rolling temperature of 935℃, and a total reduction of 81.5%, to obtain hot-rolled steel with a thickness of 12mm. Cooling treatment: The hot-rolled steel was water-cooled to room temperature; the initial cooling temperature was 940℃, and the cooling rate was 40℃ / s, resulting in a high-manganese medium-thick plate for LNG fuel tanks. The metallographic image of the high-manganese medium-thick plate for LNG fuel tanks obtained in this embodiment is shown below. Figure 1 As shown, the EBSD phase diagram is as follows: Figure 2 As shown.
[0059] Example 3 The chemical composition of low tensile strength high manganese steel for LNG fuel tanks, by mass fraction, is: C: 0.22%, Si: 0.12%, Mn: 23.20%, Al: 1.57%, with the balance being Fe and unavoidable impurities.
[0060] The preparation method of low tensile strength high manganese steel for LNG fuel tanks includes the following steps: Obtaining molten steel: According to the above-mentioned composition ratio of high manganese medium-thick plates for LNG fuel tanks, vacuum induction smelting is carried out, and argon gas is used for protection during the smelting process to obtain molten steel.
[0061] Casting process: After alloying, refine for 8 minutes and cool the molten metal to about 1500°C, then pour it into a steel mold to obtain a 20kg ingot.
[0062] The cast steel ingot is forged into a cross-sectional shape with dimensions of 65×65 mm. 2 billet Heat treatment: The billet is heated to 1200℃ in the furnace and held for 2 hours to achieve thorough homogenization.
[0063] Rolling process: The heated billet is subjected to controlled rolling in the fully recrystallized zone with an initial rolling temperature of 1125℃, a final rolling temperature of 944℃, and a total reduction of 81.5%, to obtain hot-rolled steel with a thickness of 12mm. Cooling treatment: The hot-rolled steel is water-cooled to room temperature; the starting temperature of the cooling is 940℃ and the cooling rate is 40℃ / s, to obtain high-manganese medium-thick plates for LNG fuel tanks.
[0064] Example 4 The chemical composition of low tensile strength high manganese steel for LNG fuel tanks, by mass fraction, is: C: 0.19%, Si: 0.16%, Mn: 23.30%, Al: 2.1%, with the balance being Fe and unavoidable impurities.
[0065] The preparation method of low tensile strength high manganese steel for LNG fuel tanks includes the following steps: Obtaining molten steel: According to the above-mentioned composition ratio of high manganese medium-thick plates for LNG fuel tanks, vacuum induction smelting is carried out, and argon gas is used for protection during the smelting process to obtain molten steel.
[0066] Casting process: After alloying, refine for 8 minutes and cool the molten metal to about 1500°C, then pour it into a steel mold to obtain a 20kg ingot.
[0067] Heat treatment: After the riser is removed from the ingot, it is heated to 1200℃ in the furnace and held for 2 hours to achieve a thorough homogenization process.
[0068] Rolling process: The heated billet is subjected to controlled rolling in the fully recrystallized zone with an initial rolling temperature of 1136℃, a final rolling temperature of 940℃, and a total reduction of 81.5%, to obtain hot-rolled steel with a thickness of 12mm. Cooling treatment: The hot-rolled steel is water-cooled to room temperature; the starting temperature of the cooling is 940℃ and the cooling rate is 40℃ / s, to obtain high-manganese medium-thick plates for LNG fuel tanks.
[0069] As can be seen from Table 1, Examples 1-4 reduced the tensile strength of high-manganese steel by adding Al, but significantly improved its low-temperature impact toughness and plasticity. In contrast, Comparative Examples 1-2 showed higher tensile strength but poorer plasticity and low-temperature impact toughness. Figure 1 , Figure 2 It can be seen that the austenitic structure of the high manganese steel in Example 2 is uniformly distributed, demonstrating that the high manganese steel in Example 2 is composed entirely of austenitic phase.
[0070] Comparative Example 1 The chemical composition of the Fe-Mn-C high manganese steel prepared in this comparative example, by mass fraction, is: C: 0.18%, Si: 0.14%, Mn: 23.1%, with the balance being Fe and unavoidable impurities.
[0071] The preparation method of Fe-Mn-C high manganese steel is as follows: Obtaining molten steel: According to the designed chemical composition, vacuum induction smelting is carried out according to the weight percentage. Argon gas is used for protection during the smelting process to obtain molten steel.
[0072] Casting process: After refining, the casting temperature is controlled between 1470 and 1500℃, and the molten steel is poured into a steel mold to obtain a square ingot.
[0073] Heat treatment: After the riser is removed from the ingot, it is placed in a box-type resistance furnace and heated to 1200℃ and held for 2 hours to carry out a thorough homogenization treatment, so as to reduce the segregation bands of Mn, C and other elements as much as possible.
[0074] Rolling process: After exiting the furnace, hot rolling is carried out using a hot rolling test mill. The initial rolling temperature is 1150℃, the final rolling temperature is 950℃, the total reduction rate is about 88%, and the thickness of the hot-rolled steel is 12mm. Cooling treatment: The hot-rolled steel is cooled to room temperature at a rate of 40℃ / s to obtain high-manganese steel medium-thick plates for LNG fuel tanks.
[0075] Comparative Example 2 The chemical composition of the Fe-Mn-C-Al high manganese steel prepared by comparison, by mass fraction, is: C: 0.26%, Si: 0.21%, Mn: 19.87%, Al: 0.49%, with the balance being Fe and unavoidable impurities.
[0076] The preparation method of Fe-Mn-C-Al high manganese steel is as follows: Obtaining molten steel: According to the designed chemical composition, vacuum induction smelting is carried out according to the weight percentage. Argon gas is used for protection during the smelting process to obtain molten steel.
[0077] Casting process: After refining, the casting temperature is controlled between 1470 and 1500℃, and the molten steel is poured into a steel mold to obtain a square ingot.
[0078] Heat treatment: After the riser is removed from the ingot, it is placed in a box-type resistance furnace and heated to 1200℃ and held for 2 hours to carry out a thorough homogenization treatment, so as to reduce the segregation bands of Mn, C and other elements as much as possible.
[0079] Rolling process: After exiting the furnace, hot rolling is carried out using a hot rolling test mill. The initial rolling temperature is 1150℃, the final rolling temperature is 950℃, the total reduction rate is about 88%, and the thickness of the hot-rolled steel is 12mm. Cooling treatment: The hot-rolled steel is water-cooled to room temperature; the initial cooling temperature is 940℃, and the hot-rolled steel is cooled to room temperature at a cooling rate of 40℃ / s to obtain high-manganese steel medium-thick plates for LNG fuel tanks.
[0080] Table 1. Relevant performance of Comparative Examples 1-2 and Examples 1-4 The above technical solutions of the present invention are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. All equivalent structural transformations made under the technical concept of the present invention using the contents of the present invention specification and drawings, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A low tensile strength high manganese steel for LNG fuel tanks, characterized in that, Its chemical composition by mass fraction includes: C 0.15~0.22%, Si 0.12~0.16%, Mn 23~24%, Al 1.3~2.1%, with the balance being Fe and unavoidable impurities.
2. The low tensile strength high manganese steel for LNG fuel tanks according to claim 1, characterized in that, The yield strength is 240~280MPa, the tensile strength is 620~670MPa, the impact absorption energy of the steel in the ultra-low temperature Charpy impact test along the rolling direction at -196℃ is 130~160J, and the elongation after fracture is 55~65%.
3. A method for preparing low tensile strength high-manganese steel for LNG fuel tanks, characterized in that, Including the following steps: The molten steel is obtained, and its chemical composition, by mass fraction, includes: C 0.15~0.22%, Si 0.12~0.16%, Mn 23~24%, Al 1.3~2.1%, with the balance being Fe and unavoidable impurities; The molten steel is subjected to casting, heating, rolling and cooling processes in sequence to obtain the low tensile strength high manganese steel for the LNG fuel tank.
4. The method for preparing low tensile strength high manganese steel for LNG fuel tanks according to claim 3, characterized in that, The process of obtaining molten steel includes: smelting the raw materials under a protective atmosphere to obtain the molten steel, wherein the smelting temperature is 1600~1650℃.
5. The method for preparing low tensile strength high manganese steel for LNG fuel tanks according to claim 3, characterized in that, The casting process includes: pouring the molten steel into a mold at 1470~1500℃ to obtain an ingot.
6. The method for preparing low tensile strength high manganese steel for LNG fuel tanks according to claim 3, characterized in that, The heat treatment temperature is 1150-1250℃, and the heat treatment duration is 1.5-2.5h.
7. The method for preparing low tensile strength high manganese steel for LNG fuel tanks according to claim 3, characterized in that, The initial rolling temperature during the rolling process is 1120~1150℃, and the final rolling temperature is 935~960℃.
8. The method for preparing low tensile strength high manganese steel for LNG fuel tanks according to claim 3, characterized in that, The total reduction rate during the rolling process is 75-85%.
9. The method for preparing low tensile strength high manganese steel for LNG fuel tanks according to claim 3, characterized in that, The cooling process involves a starting temperature of 940-950℃ and a cooling rate of 20-40℃ / s.
10. The method for preparing low tensile strength high manganese steel for LNG fuel tanks according to claim 3, characterized in that, The thickness of the low tensile strength high manganese steel used in the LNG fuel tank is 12±1 mm.